Development and Quality Evaluation of Ready to Serve Olive and Mandarin Blended Diet Drink: Quality Evaluation of Diet Drinks - Rehman, Atta Ur; Qazi, Ihsan Mahbood; Khan, Arsalan; Shah, Falak Naz; Shinwari, Abid Shah; Zeb, Qamar; Kaleem, Muhammad (Biological Sciences - PJSIR, 2020)
Olive (Olea europaea L.) and mandarin (Citrus reticulatae) have been used therapeutically for their nutraceutical and medicinal value. Olive juice contains high vitamin E and phenolic compounds. Similarly, mandarin is a rich source of vitamin C. Hence olive juice was blended with mandarin fruit juice for increasing the therapeutic, nutritional and functional value of Ready-to-Serve (RTS) beverages. Preliminary study revealed that Ready-to-Serve (RTS) product of olive mandarin (60:40) was highly acceptable on sensory basis by the panel of judges. Olive juice and mandarin juice were utilized at various combinations with sugar and artificial sweeteners (aspartame, sucralose and cyclamate) for preparation of therapeutic RTS beverages and evaluated for physico-chemical and sensory attributes during storage. The study revealed that the therapeutic RTS beverages prepared by blending of olive and mandarin juices with cyclamate has scored maximum for almost all sensorial quality attributes such as appearance, colour, flavour, taste and overall acceptability and also contained phenolic compounds, flavonoids and ascorbic acid in large quantity. A reducing trend was observed in ascorbic acid and increasing trend was observed in acidity content during the storage of beverage at room temperature over a period of 90 days. The beverage changed significantly with respect to TSS content along the storage period.